Perspectivas regionales del Periodo Formativo en el Perú: una introducción - Kaulicke, Peter (Pontificia Universidad Católica del Perú. Fondo Editorial, 1998)
Regional Perspectives of the Formative Period in Perú: An IntroductionThe article doesn't have an abstract
Keywords: Arqueología; Periodo Formativo; Andes Centrales; Estudios Relativos; Estado de la Cuestión; Archaeology; Formative Period; Central Andes; Related Studies; State Of The Art; https://purl.org/pe-repo/ocde/ford#6.01.02